A school-based physical activity intervention in primary school: effects on physical activity, sleep, aerobic fitness, and motor competence - Júlio A. Costa; Susana Vale; Susana Vale; Rita Cordovil; Rita Cordovil; Luís P. Rodrigues; Vasco Cardoso; Rui Proença; Manuel Costa; Carlos Neto; João Brito; José Guilherme; et al. (Frontiers Media S.A., 2024)
ObjectiveThe "Super Quinas" project evaluated the effectiveness of an intervention program to improve physical activity, aerobic fitness, sleep, and motor competence on children in primary school.MethodsThe experimental group (n = 19) enrolled in a 12-week intervention program (one more extra-curricular activity class of 60 min per week) compared to the CG (n = 19), all aged 9-10 years. Physical activity (PA) and sleep were measured by accelerometry, and aerobic fitness was measured by Children's Yo-Yo test (YYIR1C) during the 1st week (PRE), the 6th week (DUR), and the 12th week (POST) of the intervention program. Motor Competence in PRE and POST intervention was also assessed by the Motor Competence Assessment (MCA) instrument. Heart rate (HR, assessed using HR monitors), and enjoyment level were recorded during all intervention program classes. A linear mixed model analysis (i.e., within-subject analyses) was performed.ResultsComparing the EG and CG in DUR and POST, the EG spent ~18 min and ~ 34 min more time in moderate to vigorous physical activity (MVPA) per day (p < 0.001); had ~44 min and ~ 203 min less sedentary time per day (p < 0.001); performed more 44 and 128 m in the Children's Yo-Yo test compared to CG (p < 0.001) and slept more 17 and 114 min per night (p < 0.001). In POST motor competence was significantly better (27%) in the EG compared to CG (p < 0.001). The %HRmax during the extra-curricular classes ranged between 65 and 81% (i.e., light to moderate intensities), and the enjoyment between fun and great fun.ConclusionOur findings suggest that adding one more extra-curricular activity class of 60 min per week for 12 weeks effectively increased the levels of physical activity, aerobic fitness, sleep duration, and motor competence in children aged 9-10 years.